2019
DOI: 10.1186/s12889-019-7808-8
|View full text |Cite
|
Sign up to set email alerts
|

Preventing adolescent sexual harassment: evaluating the planning process in two school-based interventions using the Intervention Mapping framework

Abstract: BackgroundThe development of school-based programs for preventing adolescent sexual harassment often lacks an evidence-based approach and use of proper theories. Appropriate stakeholders are often not involved in the development process. To help improve this process, we used the Intervention Mapping framework to retrospectively evaluate the development of two school-based programs, Benzies & Batchies and Boys, each of which was intended to prevent sexual harassment among adolescent students of a lower educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
2
Order By: Relevance
“…5 Although several programs have been applied in many parts of the world, the development of school-based programs for preventing sexual harassment against adolescent girls often lacks an evidence-based approach and/or use a testable hypothesis. 3,[6][7][8][9] The development of practice-based interventions on preventing adolescent girls from sexual harassment will shed light on future development of intervention programs using an evidence-based theories with their practice-based experience. This will hopefully increase effectiveness of their interventions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although several programs have been applied in many parts of the world, the development of school-based programs for preventing sexual harassment against adolescent girls often lacks an evidence-based approach and/or use a testable hypothesis. 3,[6][7][8][9] The development of practice-based interventions on preventing adolescent girls from sexual harassment will shed light on future development of intervention programs using an evidence-based theories with their practice-based experience. This will hopefully increase effectiveness of their interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown similar environments that sexual harassment takes place. Similarly, a recent study in Nepal [ 38 ] concluded that school, roads and public places were the most common settings where participants encountered sexual harassment. In addition, college and school students, in Delhi, consider the public transport and bus stops as unsafe for them [ 13 ].…”
Section: Discussionmentioning
confidence: 91%
“…seksual berisiko memiliki konsekuensi kesehatan dan akademik yang merugikan bagi remaja dan anak muda dewasa, seperti infeksi menular seksual, kehamilan remaja, dan putus sekolah (De Lijster et al, 2019;Grossman et al, 2013Grossman et al, , 2014. Bukti yang menunjukkan bahwa program pendidikan seks komprehensif berbasis sekolah dikaitkan dengan pengurangan perilaku seksual berisiko remaja (Grossman et al, 2014).…”
Section: Perilakuunclassified